IMPROVING STUDENTS’ READING SKILL USING COMMUNICATIVE LANGUAGE TEACHING (A case study at tenth grade of SMAN 10 Depok) - Faisal Faisal (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2022)
The aims of this study are to analyze the materials and activities used in teaching reading and the result is to describe the process of improving students’ reading skill using communicative language teaching (CLT) used by the teacher at tenth grade of SMAN 10 Depok. The approach used in this study is qualitative, that is by doing observation, interviewing, and giving questionnaire. Through descriptive qualitative approach, the data of observation, interview and questionnaire are analyzed in description. Based on finding of the study,the reading material in class X MIA 1 at SMAN 10 Depok using English book 2013 curriculum. The activities in the class the teacher divided the students into groups to discussing the reading material and give conclusion or suggestion for students, it can be concluded that teaching reading using communicative language teaching can improve the student English reading skill in an English class, because the class activities were communicative. As show by the score the highest score is 95 and the lowest score 65, the average of students score in class X MIA 1 at SMAN 10 Depok is 82,2. The result from questionnaire, most students enjoy in reading class using CLT because, the teacher clearly and always gives opportunity to the students to ask the question it make students easier for understanding the text reading.